Consent for newborn screening: screening professionals' and parents' views. (January 2020) - Ulph, F.; Dharni, N.; Bennett, R.; Lavender, T.
Abstract: Objectives: Expansion of newborn bloodspot screening (NBS) within England, which practices an informed consent model, justified examining acceptability and effectiveness of alternative consent models. Study design: Qualitative focus groups. Methods: Forty-five parents and 37 screening professionals (SPs) participated. Data were analysed using thematic analysis. Results: Parents and SPs initially appeared to have differing views about appropriate consent models. Most parents accepted assumed consent, if adequately informed; however, once aware of bloodspot storage, informed consent was wanted. SPs valued informed consent, but acknowledged it was difficult to obtain. Both samples wanted parents to be informed but were unclear how this could be achieved. Most parents felt NBS was not presented as optional. Conclusion: The simultaneous exploration of parents and SPs views, in real time is original. This rigour avoided the reliance on retrospective accounts which make it difficult to establish how decisions were made at the time. It is also unique in providing pre-interview consent models to drive the depth of data. It was rigorous in member checking. Findings suggested a preference for full disclosure of all information with some parents valuing this more than choice. Both samples queried whether current consent was sufficiently informed and voluntary. Results suggest differing tolerances of consent type if screening is solely for diagnostic purposes vs bloodspot storage. Results highlight the need for caution when examining consent model preferences without also checking knowledge, as opinions may be based on incomplete knowledge. Future research is needed to examine efficacy of proposed changes. Funding: National Institute for Health Research Health Technology Assessment HTAProgramme (11/62/02). Trial registration: ISRCTN70227207. Highlights: Participants preferred consent models they believed ensured parents were informed. Indeed information was more valued than choice for some. Parents value newborn screening, but this may be based on a belief of screening confirming a state of health. Parents are often unaware of their choice, potential outcomes or sample storage. Prioritising information about choice and storage may increase information engagement.